"I (Don't) Respect My Body": Investigating the Role of Mass Media Use and Self-Objectification on Adolescents' Positive Body Image in a Cross-National Study. Issue 1 (2nd January 2021) - Karsay, Kathrin; Trekels, Jolien; Eggermont, Steven; Vandenbosch, Laura
ABSTRACT: This cross-national survey among Austrian, Belgian, Spanish, and South Korean boys and girls ( N = 1, 983; M age  = 14.41, SD  = 1.08) investigated the association between mass media use, self-objectification, and positive body image. In doing so, we (a) extended existing research on the link between media use and positive body image by including different media genres that are known to be part of adolescents' media diets, (b) introduced self-objectification as a potential mediator, (c) differentiated between boys and girls, and (d) tested these assumptions across diverse cultural settings. Overall, our findings suggest that the use of different types of media that emphasize physical beauty and (sexual) appearance relate both negatively as well as positively to adolescents' appreciation of their own body. Self-objectification (i.e., valuing one's appearance characteristics over competence/functionality characteristics) is negatively related to adolescents' positive body image, indicating a mediating mechanism. Our results highlight the need for further research on the content of mass media and a positive body image.